Proceedings of the 9th World Construction Symposium 2021 on Reshaping Construction: Strategic, Structural and Cultural Transfor 2021
DOI: 10.31705/wcs.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Skills Between Sri Lankan and Foreign Construction Labour

Abstract: Construction significantly influences a country’s economy. The labour efforts are the lifeblood of construction operations. The construction industry has been facing many challenges due to skill shortages in many countries. This study aimed to compare the work-related skills of Sri Lankan labour against foreign labour forces. A qualitative study methodology was adopted through literature reviews and expert interviews to identify the labour skills which influence the productivity of construction operations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 8 publications
(10 reference statements)
0
29
0
Order By: Relevance
“…This significantly contributes to the improvement of labour productivity in construction activities, but the level of enthusiasm that most Sri Lankan labourers have towards their assigned tasks at their workplaces is inadequate. By comparing with Arabian, Chinese, Korean and Malaysian labour forces, which were the leading foreign labour forces in the skill-based ranked list, Manoharan et al. (2021b) highlighted the significant need for improving the commitment of Sri Lankan labourers in construction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This significantly contributes to the improvement of labour productivity in construction activities, but the level of enthusiasm that most Sri Lankan labourers have towards their assigned tasks at their workplaces is inadequate. By comparing with Arabian, Chinese, Korean and Malaysian labour forces, which were the leading foreign labour forces in the skill-based ranked list, Manoharan et al. (2021b) highlighted the significant need for improving the commitment of Sri Lankan labourers in construction.…”
Section: Resultsmentioning
confidence: 99%
“…The industry consultative experts stated that the cognitive skills of Sri Lankan labourers in various technical operations (specifically concreting, bar bending, plastering, tiling, welding, electrical works and equipment handling) are required to be significantly improved. Manoharan et al (2021b) also revealed that the construction training institutions need to have a special focus on the cognitive skills of labourers in concreting, bar bending, plastering, plumbing, tiling, welding, electrical works, understanding drawings, material handling and equipment handling. Praveen et al (2011) highlighted that the labourers' poor knowledge of understanding drawings and material handling significantly affected the progress of construction activities in Sri Lanka.…”
Section: Lack Of Knowledge/cognitive Skills Of Labourers In Construct...mentioning
confidence: 99%
See 1 more Smart Citation
“…ISSC also particularly highlighted the poor cognitive and job-specific technical skills of the Sri Lankan labourers in recent scenarios. Manoharan et al [43] have accentuated the need for improving the cognitive and self-management skills of Sri Lankan labourers through a systematic comparison of the work-related skills between Sri Lankan labour and other leading foreign labour forces, namely Arabian, Chinese, Korean and Malaysian. Manoharan et al [43] have also revealed that construction training institutions in Sri Lanka need to have a special focus on the technical skills of labourers in concreting, bar bending, plastering, tiling, welding, electrical works and equipment handling.…”
Section: Lack Of Training Facilities For Labourersmentioning
confidence: 99%
“…Vocational Education Commission [25] and Manoharan et al [43] highlighted the need of upgrading the construction supervisory training programmes in the Sri Lankan construction industry with special attention on improving the self-management and transferable skills of construction supervisors.…”
Section: 4mentioning
confidence: 99%